Aktualisasi Sufisme dan Masa Depan Pendidikan Islam Modern Era Society 5.0 - Adibah, Ida Zahara; Chasanah, Uswatun (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2023)
Education always develops following the dynamics of people's lives, Islamic education is faced with big challenges after the industrial revolution 4.0 era, then "is surprised by the emergence of the era of society 5.0 where at this time there appears a "learning society" and a society with knowledge (knowledge). society). This qualitative study aims to find out how to actualize Sufism and the future of modern Islamic education in the era of society 5.0. The world of education takes a large part of the teachings of Islamic Sufism because Sufism teaches respect for fellow creatures of God without discriminating against a background, leading people to be tolerant and upholding peace. With data collection methods, namely observation, and interviews. The results of the research information that Islamic education will form Insan Kamil, which has a close relationship with the essence of modern Sufism, namely with the creation of life, and simplicity (zuhud) from within a modern Sufism, which is based on the principle of monotheism, so that it can realize an attitude of piety, which later will maintain good relations with God, fellow humans, the universe or the surrounding environment. From the results of the research that has been submitted, it is hoped that in modern conditions and the era of society 5.0, the practice of Sufi is very necessary, but the meaning is not as narrow as what has been understood, meaning Sufi does not mean isolating oneself from communication in the mass media. People with different beliefs, different languages, cultures, and ethnicities, are still human beings who must be respected, appreciated, and accepted for their existence.